2022
DOI: 10.1038/s41598-022-20447-6
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]FAPI-PET/CT for radiation therapy planning in biliary tract, pancreatic ductal adeno-, and adenoidcystic carcinomas

Abstract: Biliary-tract-carcinomas (BTC), pancreatic-ductal-adenocarcinomas (PDAC) and adenoidcystic-carcinomas (AC) have in common that they are traditionally treated with large clinical-target-volumes (CTV). The aim of this study is to examine the impact of pretreatment-[68Ga]FAPI-PET/CT on target-volume-definition and posttreatment-[68Ga]FAPI-PET/CT-response-assessment for BTC-, PDAC- and AC-patients referred to radiation-therapy. All consecutive BTC-, PDAC-, and AC-patients who received pretreatment-[68Ga]FAPI-PET/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, 68 Ga-FAPI uptake can not only be seen in CAF, but also in non-malignant conditions, such as inflammatory lymph nodes, artherosclerosis, or surgical scars [59]. Nevertheless, the high tracer uptake is described in 68 Ga-FAPI PET images obtained from human PDAC patients [22,60]. CAFs have been identified as a target in tumor diagnosis and therapy, as they seem to play a key role in various parts of tumor development, such as tumor growth, metastasis formation, and the immune response [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 68 Ga-FAPI uptake can not only be seen in CAF, but also in non-malignant conditions, such as inflammatory lymph nodes, artherosclerosis, or surgical scars [59]. Nevertheless, the high tracer uptake is described in 68 Ga-FAPI PET images obtained from human PDAC patients [22,60]. CAFs have been identified as a target in tumor diagnosis and therapy, as they seem to play a key role in various parts of tumor development, such as tumor growth, metastasis formation, and the immune response [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, volumetric parameters derived from 18 F-FDG PET/CT have a great potential to improve the assessment of response to therapy [27][28][29]. In a recent study in patients with pancreatic cancer, it was reported that radiotherapy planning and evaluation of response to treatment improved significantly with volume-based 68 Ga-FAPI-04 PET/CT [30]. In our study similar to the literature, we found that 68 Ga-FAPI-04 PET/CT was superior to 18 F-FDG PET/CT in the volume-based evaluation of primary tumors and their metastases.…”
Section: Discussionmentioning
confidence: 99%